2019
DOI: 10.1136/thoraxjnl-2018-212514
|View full text |Cite
|
Sign up to set email alerts
|

Changing causes of death for patients with chronic respiratory disease in England, 2005-2015

Abstract: BackgroundChronic respiratory diseases (CRD) are common, are increasing in prevalence, and cause significant morbidity and mortality worldwide. However, we have limited knowledge on causes of death of patients with CRD in the general population.ObjectiveWe evaluated mortality rates and causes of death over time in patients with CRD.MethodsWe used linked primary care and mortality data to determine mortality rates and the most common causes of death in people with CRD (including asthma, bronchiectasis, COPD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
2
25
1
1
Order By: Relevance
“…This uses data on the presence or absence of 20 diseases, and performs slightly better than the Charlson co-morbidity index. The deaths of up to two thirds of COPD patients are thought to be due to co-morbidities [ 7 10 ]. However, existing COPD prognosis models that include co-morbidities have been developed either in small cohorts, or in populations unrepresentative of general practice or with small lists of co-morbidities [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This uses data on the presence or absence of 20 diseases, and performs slightly better than the Charlson co-morbidity index. The deaths of up to two thirds of COPD patients are thought to be due to co-morbidities [ 7 10 ]. However, existing COPD prognosis models that include co-morbidities have been developed either in small cohorts, or in populations unrepresentative of general practice or with small lists of co-morbidities [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among individuals with chronic obstructive pulmonary disease (COPD), multimorbidity is common. In addition to the most common comorbidity, cardiovascular disease (CVD), diabetes mellitus (DM), and anxiety/depression (A/D) are also more common among subjects with than without COPD, 13 and population-based studies have shown a higher mortality among individuals with than without COPD, 4,5 but the known under-diagnosis of COPD 6,7 contributes to an underestimation of the mortality among subjects with COPD in register-based studies. Even though respiratory failure is common in severe COPD, 8 comorbidities probably contribute to the increased mortality observed among individuals with mild-to-moderate COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Im Raucherstatus unterschieden sich die Kohorten nicht. Betrachtet man Todesursachen in England zwischen 2005 und 2015, so starben Asthmatiker zu etwa 20 % an kardiovaskulären Erkrankungen, was etwas seltener war als in der Allgemeinbevölkerung [49]. Eine Meta-Analyse von 11 Studien mit mehr als 550 000 Personen zeigte bei Asthmatikern eine Odds Ratio von 1,9 für kardiovaskuläre Komorbidität und eine OR von 1,4 für zerebrovaskuläre Komorbidität im Vergleich zu Personen ohne Asthma [50].…”
Section: Kardiale Komorbidität Beim Asthma Bronchialeunclassified